(untitled) (Materiali di Estetica. Terza serie, 2017)
With the distance of sixty years since the publication of La poétique de l’espace (1957), this may be the occasion to discriminat the contibution of Gaston Bachelard to an ontology of the poetic of phenomenological orientation. Reacting to the abuses perpetrated by the application of the psychoanalysis to the singularities of poetic creation, Bachelard founds a kind of aesthetic ethics fucused on embracing the image in its status of origin and event, freeing it from causalistic determinations. It is not the question of the origin, but the attitude of attachment that admires it in its ontological excess, wich allows us to participate in the poetic image closing with it rationalizing distances. In order to evaluate the specificity of the corpus elaborated by Bachelard between 1957 and 1962, we also mentioned certain contributions due to Kant, Baudelaire and Lautréamont concerning the sovereingnty of the creative imagination.